ANALISIS TINDAK TUTUR ILOKUSI PADA FILM IMPERFECT KARYA ERNEST PRAKASA DAN MEIRA ANASTASIA SEBAGAI ALTERNATIF BAHAN AJAR TEKS DRAMA SMA KELAS XI: penelitian tindak tutur ilokusi - Risna Dara; Dr. Any Budiarti, M.Hum.; Rendy Triandy, M.Pd (STKIP Subang, 2023)
This research aims to analyze the illocutionary speech acts in the imperfect film; determine the speech acts contained in the imperfect film and associated with the form and function of illocutionary speech acts, namely assertive, directive, expressive, commissive, and declarative; describe the form of Learner Worksheet (LKPD) that utilizes the results of the research. The method used in this research is descriptive qualitative. The writer analyzes the form of illocutionary speech acts in imperfect film and finds 101 utterances. However, there are 12 utterances that have two illocutionary speech acts so there are 113 data including 34 assertive sentences, 26 directive sentences, 41 expressive sentences, 3 commissive sentences, and 9 declarative sentences. Data on the function of illocutionary speech acts found 36 data which is the function of illocutionary speech acts, including 19 competitive functions, 8 convival functions, 8 collaborative functions, and 1 conflictive function. This indicates that the imperfect film is appropriate and fulfills all the functions of illocutionary speech acts. The analysis shows that there are many forms of illocutionary speech acts in the movie, especially in expressive sentences and the most speech act functions are competitive functions. The author utilizes the research results as teaching materials for drama texts of grade XI. The results of the analysis used as teaching modules and LKPD are valid with a score of 96 from the first validator and 92 from the second validator, so it is feasible to be used as teaching materials in Indonesian language learning for grade XI high school students.